2015
DOI: 10.3844/jmssp.2015.52.60
|View full text |Cite
|
Sign up to set email alerts
|

Zero Inflated Poisson and Geographically Weighted Zero- Inflated Poisson Regression Model: Application to Elephantiasis (Filariasis) Counts Data

Abstract: Poisson regression has been widely used for modeling counts data. Violation of equidispersion assumption can occur when there are excess of zeros of the data. For that condition we can use Zero-Inflated Poisson (ZIP) to analyze such data, resulting global parameter estimates. However spatial data from various locations have their own characteristics depend on their socio-cultural, geographical and economic conditions. In this paper, we first review the theoretical framework of Zero-Inflated Poisson (ZIP) and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Two studies 17 18 examined but did not identify any spatial dependence in their dataset. One study 19 did not identify spatial autocorrelation, but identified weak spatial heterogeneity. Based on these results, the authors decided to incorporate spatial terms in the model to predict LF prevalence.…”
Section: Outputsmentioning
confidence: 99%
“…Two studies 17 18 examined but did not identify any spatial dependence in their dataset. One study 19 did not identify spatial autocorrelation, but identified weak spatial heterogeneity. Based on these results, the authors decided to incorporate spatial terms in the model to predict LF prevalence.…”
Section: Outputsmentioning
confidence: 99%
“…Terdapatnya faktor spasial atau geografis dalam penyebaran malaria di berbagai wilayah. Perbedaan kondisi geografis di setiap wilayah, karakteristik masyarakat dan perekonomian masing-masing wilayah dapat menyebabkan adanya heterogenitas spasial (Purhadi et al, 2015). Untuk kasus yang terdapat heterogenitas spasial, maka metode tersebut dikembangkan dengan menambahkan faktor spasial yaitu Geographically Weighted Zero-Inflated Poisson Regression (GWZIPR).…”
Section: Pendahuluanunclassified
“…Penelitian terkait dengan GWZIPR telah dilakukan sebelumnya oleh Kalogirou [9] dengan hasil penelitian bahwa metode GWZIPR terbukti secara empiris lebih baik dalam menjelaskan tujuan para migran internal di Athena dibandingkan dengan ZIP. Penelitian lainnya dilakukan oleh Purhadi dkk [12] yang menunjukkan hasil berdasarkan uji F,GWZIPR dan ZIPR tidak berbeda secara signifikan. Adeliana [10] pada skripsinya mengestimasi parameter GWZIPR menggunakan data penderita penyakit tetanus neonatorum di seluruh kabupaten/kota di Provinsi Jawa Timur yang dipengaruhi oleh empat faktor secara signifikan yaitu cakupan imunisasi TT2+ terhadap jumlah ibu hamil, ibu bersalin ditolong tenaga kesehatan, cakupan kunjungan neonatal lengkap terhadap jumlah bayi, dan penangan komplikasi neonatal terhadap jumlah ibu hamil.…”
Section: Zero Inflated Poisson Regression (Zipr) Dikenalkan Oleh Lambert Untuk Mengatasi Data Cacahan Yang Memiliki Excess Zerosunclassified